Neuere Aspekte der Physikalischen Chemie: Dynamische Phänomene und instabile Moleküle - Hans Fischer (CHIMIA)
In the last 2 decades a gradual change of the research and teaching objects of physical chemistry is noticed: The study and description of microscopic chemical systems become favoured over those of macroscopic systems. This trend is due to a rapid development of the appropriate physical techniques, and is further stimulated by the closer interaction between physical chemistry and the other chemical sciences. Research examples are presented to illustrate some of these points. They deal with enols in photochemistry, radical termination rates in liquids and muonium chemistry.